EVALUATION OF ANTIMICROBIAL ACTIVITIES OF GOATS, BUFFALO AND HORSE MILK - I., Oktaviani; Sukmawati, N.M.S.; Lindawati, S.A. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine differences in antimicrobial activity between goat, buffalo and horse milk, as well as milk which has the highest antimicrobial activity. The experimental design used was a completely randomized design (CRD) consisting of three treatments and five replications. The three treatments were: goat milk (L1), buffalo milk (L2) and horse milk (L3). The variables observed were antimicrobial activity against Staphylococcus aureus ATCC 3351 and Escherichia coli ATCC 8739, pH value, and total lactic acid bacteria (LAB). The results showed that the antimicrobial activity in the L1, L2, and L3 treatments showed a significant difference (P<0.05) against Staphylococcus aureus ATCC 3351 and Escherichia coli ATCC 170 8739 with clear zone diameters of 28.44 mm and 29 mm respectively. 29.49 mm in the L2 treatment, while L1 and L3 had no clear zones. The pH value and total LAB also showed a significant difference with a value of 6.65 in the L1, 6.77 (L3) and 6.90 (L2) treatments. The total lactic acid bacteria in the L1, L2 and L3 treatments were 2.7 x 103; 5.5 x 104; and 9.2 x 104 CFU/ml. The conclusion of this study is that goat, buffalo and horse milk have different antimicrobial activity, while buffalo milk has the highest antimikrobial activity.